The Parotid Gland is an Underrecognized Organ at Risk for Craniospinal Irradiation. (June 2016) - King, Martin T.; Modlin, Leslie; Million, Lynn; Donaldson, Sarah S.; Gibbs, Iris C.; Choi, Clara Y. H.; Soltys, Scott G.
Purpose: Current craniospinal irradiation (CSI) protocols do not include the parotid gland as an organ at risk, potentially leading to late effects of xerostomia and secondary parotid malignancies. We analyzed the effect of CSI treatment parameters on parotid dose. Materials and Methods: We retrospectively reviewed 50 consecutive patients treated with CSI to an intracranial dose >26 Gy. Parotid dose was compared to a Radiation Therapy Oncology Group (RTOG) dose constraint (at least 1 parotid with mean dose <26 Gy). The effects of CSI dose (≤24 Gy vs 24 Gy), volumetric-modulated arc therapy (VMAT) versus 3-dimensional (3D) CSI technique, boost dose (≤24 Gy vs 24 Gy), supratentorial versus infratentorial boost location, intensity-modulated radiation therapy (IMRT)-based versus 3D boost technique, supine versus prone position, and age on parotid dose were analyzed using multivariate regression analysis. Results: The RTOG parotid dose constraint was exceeded in 22 (44%) of 50 patients. On multivariate regression analysis, lower CSI dose and VMAT CSI technique were associated with reduced parotid dose for the CSI fields. For the boost fields, lower boost dose and supratentorial boost location were associated with lower parotid dose. All 5 patients who underwent VMAT CSI met dose constraints. Furthermore, for infratentorial lesions with a total (CSI plus boost) dose prescription dose >50 Gy (n = 24), 11 of 16 patients who received low-dose CSI (18-23.4 Gy) were able to meet dose constraints, when compared to only 2 of 8 patients who received high dose CSI (36 Gy). Conclusion: Given the large number of patients exceeding the parotid dose constraint, the parotid gland should be considered an organ at risk. CSI dose de-escalation and IMRT-based CSI techniques may minimize the risk of xerostomia.